Morphological Characterization and genetic Diversity of Macrobrachium rosenbergii (De Man, 1879) Crossbreeding Result from Samas, Bone, and Sintetis Populations - Trijoko .; Niken Satuti Nur Handayani; Anggun Feranisa (Jurnal Sain Veteriner, 2013)
Abstract In Indonesia, research for the prime seed of Macrobrachium rosenbergii crossbreeding is rarely done. The aims of this study are to study F1's morphological character and genetic diversity from the result of crossbreeding between M.rosenbergii Samas, Bone, and Sintetis populations. In this study, genetic characterization was known by using PCR RAPD method utilizes three primers and morphological characterization. Data were analysed with UPGMA algorithm and Simple Matching coefficient that were presented in dendrogram. F1's coefficient heterosis was counted based on ratio from the average of cephalothorax and abdoment lenght and also ratio from the average of standard length of charapax and the average of abdomen length. The results showed that there was a very high genetic diversity in F1 population. The specific locus was found in individuals from Sintetis and Samsam populations.100% Polimorfism was found from F1's DNA amplification result, meanwhile monomorphism 50% was found from parent's DNA amplification result on OPA 20. The highest F1 heterosis was found in Samas and Sintetis genotipe.